How the South African media’s engagement with think tanks shaped coverage of the Russia-Ukraine war - Karrim, Qudsiya (University of the Witwatersrand, Johannesburg, 2024)
Research on the relationship between media and think tanks points to evidence of an interdependent and mutually beneficial arrangement. Think tanks offer their expertise in return for exposure, but factors such as professional credibility, the resources at their disposal and their adherence to media logics impact the success of this exchange. To explore the think tank-media nexus in South Africa, this study draws on agenda building and source theories to examine the ways in which three South African news sites utilised think tanks in their coverage of the Russia-Ukraine war. Through a thematic analysis and purposively selected interviews with media and think tank staff, it details a range of engagements between journalists and experts that occurred on the public record and behind the scenes. Think tanks served as high-value sources, content producers and educational tools for the media. This is not only indicative of their agenda-building influence, but also highlights how experts are playing a compensatory role in under-resourced newsrooms.
A research report submitted in fulfillment of the requirements for the Master of Arts by Coursework and Research Report in Journalism and Media Studies, In the Faculty of Humanities, Wits School of Art, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Agenda building; media-source relationships; Russia-Ukraine war; South African media; think tanks; SDG-4: Quality education